Research evaluation of family mediation practice and the issue of violence: Final Report - Australia. Office of Legal Aid and Family Services; Keys Young (Firm) (Canberra : Attorney-General's Dept., 1996)
The aim of the study was to look into issues of family violence confronting family mediation services; provide information on the extent to which violence is an issue in the population who wish to mediate, and identify the various responses of mediation agencies; identify outcomes and client satisfaction for clients for whom violence has been/is an issues and for those not accepted for mediation because of violence or other issues; identify relevant issues for policy; and to make proposals as to staff education and training.
8.3.13. Follow-up after mediation is concluded -- 8.4. A framework for training -- 8.4.1. National training program -- 8.4.2. Program development -- 8.4.3. 'Train the trainer' program -- 8.4.4. Role of trainers at agency level -- 8.4.5. Relationship between training and agency practice -- 8.4.6. Content of training -- Appendix A. Women's exist survey -- Appendix B. Women's qualitative interviews -- Appendix C. Questions for key informants and referral agencies -- Appendix D. Men's exit survey -- Appendix E. Family Law Reform Act 1995 overview information sheet / prepared by Attorney-General's Department, May 1996. warni.ncil discovered
Bibliography: p. 133-135
Keywords: Family violence -- Australia; Family mediation -- Australia; Family mediation -- Evaluation